Integration of the first physician assistants into Israeli emergency departments - the physician assistants' perspective - Rina Maoz-Breuer; Oren Berkowitz; Rachel Nissanholtz-Gannot (BMC, 2019)
Abstract Background A new role of Physician Assistant (PA) was introduced into Emergency Departments (ED) in Israel in 2016, as part of a larger effort to improve the quality of service in the EDs. When the new role was introduced, there was a fair amount of uncertainty about whether it would succeed, in light of ambivalence on the part of many ED nurses, and lack of clarity among ED directors about the necessity of a PA role, and about the extent to which PAs would be allowed to take on professionally meaningful tasks. The first class to train PAs was run by the Ministry Of Health between May 2016 and August 2017, with 34 PA trainees participating. 17 out of 24 EDs across Israel partook in the integration of the new PAs. This study assessed how this initial phase of integration is proceeding, from the perspective of the PA trainees themselves. Methods New PA trainees were surveyed at the beginning and end of their training. Likert scale responses were collected (using a scale of 1 to 6). Respondents were asked about difficulties in their previous profession, their motives for choosing the PA profession and their expectations for the new position. The follow-up survey included additional questions about their clinical activities. Descriptive and correlational statistics were performed. Results In the first survey, PA trainees reported that their main difficulties as paramedics were lack of options for professional advancement and burnout. New PA trainees had initially very high expectations for professional challenge, professional status upgrade, personal fulfillment, career prospects and an increase in wages (average mean score 5.7). In the follow-up survey there was a large drop in all of their ratings (average mean score 3.8). In the second survey, PA trainees reported spending the majority of their time evaluating, diagnosing and managing patients as opposed to preforming clinical procedures, such as inserting an IV, administrating medicine or applying casts. Despite their decreased expectations, they still felt that they were intellectually stimulated (5.3 average), given high levels of responsibility (4.8 average), and making significant contributions to the healthcare team and patients (average score of 5.5). All of the above were correlated with overall satisfaction. The main difficulties they reported were related to limited authority and further career advancement. Conclusions The new Israeli PA role has officially been launched in emergency medicine. The first group of PA trainees report a positive, productive integration, and overall satisfaction levels with their new career are high. However, the PA trainees reported having experienced some difficulties along the way, and there was a large decrease in their overall expectations from the new position during their first year on the job. Since the subject of limited authority was found to be a substantial difficulty for the new PA trainees, the Ministry of Health should explore this issue and create a uniform policy on it.